Why we can't wait - King, Martin Luther, Jr., 1929-1968.; Jackson, Jesse, 1941- (New York : Signet Classic, 2000)
This paperback reissue of a classic not only examines King's Birmingham campaign for civil rights, but the history of the struggle and the tasks that await future generations fighting for equality. New Afterword by Rev. Jesse Jackson. Reissue.
Negro Revolution--why 1963? -- Sword that heals -- Bull Connor's Birmingham -- New day in Birmingham -- Letter from Birmingham jail -- Black and white together -- Summer of our discontent -- Days to come.
Includes bibliographical references (pages 154-155) and index.
Keywords: African Americans -- Civil rights; African Americans -- Civil rights; Droits; Politique et gouvernement; African Americans -- Civil rights